Assessment of the Clinical Diagnosis of Onychomycosis by Dermoscopy - Ma, Yan; Ji, Ying; Cen, Wen; Qiao, Zusha; Gao, Yan; He, Lu; Feng, Wenli (Frontiers in Surgery, 2022)
Background. As a common clinical superficial fungal infection, the diagnosis of onychomycosis relies on clinical features, traditional KOH direct microscopy and fungal culture. In recent years, dermoscopy has been widely used in the diagnosis and treatment of infectious diseases and has provided new options for the diagnosis of onychomycosis. Objective. To evaluate the value of dermoscopy in the clinical diagnosis of onychomycosis and to explore the relationship between each clinical subtype and the dermoscopic pattern. Methods. A retrospective study of 114 cases of clinically suspected onychomycosis was conducted to compare the differences between dermoscopy and fungal pathogenic examination (microscopy and culture) in the diagnostic sensitivity of onychomycosis and to analyse the relationship between nine common dermoscopic modalities and clinical subtypes of onychomycosis. Results. Among the 114 proposed patients, 87 nails with positive fluorescent staining microscopy and/or positive fungal cultures were diagnosed as onychomycosis. The sensitivity and specificity of dermatoscopy, using the mycological findings as a reference, were 86.21% and 33.33% respectively. The incidence of common dermatoscopic patterns in the 87 nails with confirmed onychomycosis was as follows: white flocculation in 76 cases (87.35%), longitudinal nail pattern in 72 cases (82.76%), jagged changes in the distal nail plate in 69 cases (79.31%) and yellow staining in 46 cases (52.87%), these four patterns were more commonly seen in the distal lateral subungual onychomycosis and total dystrophic onychomycosis, but there was no statistical difference in the positive dermatoscopic pattern between these two types (P>0.05). Conclusion. Dermoscopy can be an important aid in the diagnosis of onychomycosis, especially when fungal microscopy or culture is not appropriate, but this method is still not a substitute for fungal microscopy and culture.